Overview of Self-Adjustment of New Students of Nursing Study Program Students at Santa Elisabeth Collage of Health Sciences Medan - Mardiati Barus; Vina Yolanda Sari Sigalingging; Adria Evicarolina Gea (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Self-adjustment is an interaction ability to establish a good relationship between individuals and their environment. New student self-adjustment is a challenge to deal with changes from high school to college. Changes in terms of academic, social, emotional and institutional attachment are much more difficult than the previous level of education so that new students have difficulty adjusting. This study aims to determine the description of the self-adjustment. Methods: The type of research design used is descriptive with a cross sectional design. The instrument used is a questionnaire with google form media. The population in this study are 99 respondents. The sampling technique uses total sampling technique with a sample size of 99 respondents. Results: Based on the results of the study analyzed using univariate analysis, it shows that new students have a high level of self-adjustment, namely 68 people (68.7%) and moderate self-adjustment as many as 31 people (31.3%). Low self-adjustment can be caused by self-doubt, lack of self-confidence, lack of openness from others and excessive stress. Conclusion: So the researcher expects new students to multiply relationships, improve talents and skills, follow guidance during the learning process in lectures and seek support and motivation from mentors, friends, and family.